# am_lect_18 - 1 P(0 2 ∀ k ∈ N ∀ m ≤ k P m → P k 1...

This preview shows pages 1–3. Sign up to view the full content.

Induction: A geometric example A triomino is a 2 × 2 square with one square missing: Claim : n 1, any 2 n × 2 n checkerboard with one square missing can be tiled with triominos Proof by induction on n : Base case ( n = 1): A 2 1 × 2 1 checkerboard with one square missing is a triomino, so it can obviously be tiled Inductive step: Let k N such that any 2 k × 2 k checkerboard with one square missing can be tiled with triominos [IH] Consider a 2 k +1 × 2 k +1 checkerboard with one square missing. This is clearly made up of three complete 2 k × 2 k checkerboards and one 2 k × 2 k checkerboard with one square missing. Place one triomino so that it covers one square of each complete checkerboard. We are left with the problem of tiling four 2 k × 2 k checkerboard each “missing” one square, which can by done by the IH. This completes the proof by induction.

This preview has intentionally blurred sections. Sign up to view the full version.

View Full Document
Strong Induction Normal induction: In order to prove: n N , P ( n ) … we prove two things: 1) P (0) 2) k N , P ( k ) P ( k +1) Strong induction: In order to prove: n N , P ( n ) … we prove two things:
This is the end of the preview. Sign up to access the rest of the document.

Unformatted text preview: 1) P (0) 2) ∀ k ∈ N , ( ∀ m ≤ k , P ( m )) → P ( k +1) Inductive hypothesis Strong inductive hypothesis Example Claim : Every postage value n ≥ 12 cents can be made up of 4-cent and 5-cent stamps — Mathematically, ∀ n ≥ 12, ∃ a ∈ N , ∃ b ∈ N , n = 4 a + 5 b Proof by induction on n : Base cases ( n = 12, 13, 14, 15): Since 12 = 4 × 3+5 × 0, 13 = 4 × 2+5 × 1, 14 = 4 × 1+5 × 2, 15 = 4 × 0+5 × 3, the base cases all hold. Inductive step: Let k ≥ 15 such that ∀ m ≤ k and m ≥ 12, ∃ a ∈ N , ∃ b ∈ N , m = 4 a + 5 b [strong IH] We need to show that ∃ p ∈ N , ∃ q ∈ N , k +1 = 4 p + 5 q Now k +1 = ( k − 3)+4. Since k ≥ 15, k − 3 ≥ 12 and hence by the strong IH, ∃ a ∈ N , ∃ b ∈ N , k − 3 = 4 a + 5 b Hence k +1 = 4 a + 5 b + 4 = 4( a +1) + 5 b . Hence the statement holds for k +1, which completes the proof by (strong) induction....
View Full Document

{[ snackBarMessage ]}

### Page1 / 3

am_lect_18 - 1 P(0 2 ∀ k ∈ N ∀ m ≤ k P m → P k 1...

This preview shows document pages 1 - 3. Sign up to view the full document.

View Full Document
Ask a homework question - tutors are online